A Novel Organo-Selenium Bandage that Inhibits Biofilm Development in a Wound by Gram-Positive and Gram-Negative Wound Pathogens - Tran, Phat L. (Antibiotics (Basel), 2014)
Biofilm formation in wounds is a serious problem which inhibits proper wound healing. One possible contributor to biofilm formation in a wound is the bacteria growing within the overlying bandage. To test this mechanism, we used bandages that contained a coating of organo-selenium that was covalently attached to the bandage. We tested the ability of this coating to kill bacteria on the bandage and in the underlying tissue. The bandage material was tested with both lab strains and clinical isolates of Staphylococcus aureus, Pseudomonas aeruginosa and Staphylococcus epidermidis. It was found that the organo-selenium coated bandage showed inhibition, of biofilm formation on the bandage in vitro (7–8 logs), with all the different bacteria tested, at selenium concentrations in the coating of less than 1.0%. These coatings were found to remain stable for over one month in aqueous solution, 15 min in boiling water, and over 6 years at room temperature. The bandages were also tested on a mouse wound model where the bacteria were injected between the bandage and the wound. Not only did the selenium bandage inhibit biofilm formation in the bandage, but it also inhibited biofilm formation in the wound tissue. Since selenium does not leave the bandage, this would appear to support the idea that a major player in wound biofilm formation is bacteria which grows in the overlying bandage.